Pharmacophore-based molecular docking and in-silico study of novel usnic acid derivatives as avian influenza A (H7N9) inhibitor - Roney, Miah; Wong, Kelvin Khai Voon; Huq, A. K. M. Moyeenul; Rullah, Kamal; Saiful Nizam, Tajuddin; Hazrulrizawati, Hamid; Mohd Fadhlizil Fasihi, Mohd Aluwi (The Official Publication of The Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2022)
The Avian Influenza virus is not only dangerous to birds, but it is also dangerous to people and other animals. It is a serious danger to poultry worldwide with the capacity to spread to other species, including people; consequently, more efficient medicines are required to treat this virus. This study examined the binding effectiveness of twentyone (21) Usnic acid derivatives out of 340 generated via pharmacophore filtering with AIV A (H7N9) utilising an in-silico technique. The docking simulation to AIV A obtained five compounds with a high affinity to the target protein. The ADMET and druggability prediction produced two lead molecules that were then submitted to Cytochrome (CYP) P450 enzyme screening to generate the best molecule, labelled as compound 5. According to the findings, compound 5 might be employed as a lead inhibitor in developing an anti-AIV medication